(untitled) (Jurnal Bahasa, 2018)
The Perak dialect is spoken in an area stretching from Kuala Kangsar to central and lower Perak. Even though the dialects of these three areas have similarities and are categorized as one dialect, each area has its own sub-dialects. This paper is a descriptive analysis of the northern Perak dialect, and seeks to identify the forms and status of question words in this dialect. The methodology used in this research was to obtain data from respondents in Kampung Sayong Lembah and Kampung Simpang Melembu. The research shows that the question words in the northern Perak dialect differ slightly from those of standard Malay but can still be comprehended by others. The differences that can be seen are the question words can occur in the initial, medial and final positions in a sentence. This shows that there is variation in the Perak dialect. Keywords: question words, dialect, northern Perak, syntax, descriptive